Museums, collections, exhibitions and indigenous people - van Velthem, Lucia Hussak (2018)
Anthropological studies, in their most current tendencies, began to focus on museological theory and the practices conducted in museum spaces, which are understood as sites that carry the marks of specific productions. Thus, in ethnographic museums, the custody or exhibition of their collections are carried out in territories that produce some of these marks, since they are characteristic of these institutions. This article discusses the links that the anthropological museums establish with their ethnographic collections, in the spaces of the technical reserve and the exhibition highlighting some of the meanings that mark them and define them. The methodology used was documentary and ethnographic research.